Exercise-induced anti-obesity effects in male mice generated by a FOXO1-KLF10 reinforcing loop promoting adipose lipolysis - Jie-Ying Zhu; Min Chen; Wang-Jing Mu; Hong-Yang Luo; Yang Li; Shan Li; Lin-Jing Yan; Ruo-Ying Li; Meng-Ting Yin; Xin Li; Hu-Min Chen; Liang Guo (Nature Communications)
Abstract Exercise combats obesity and metabolic disorders, but the underlying mechanism is incompletely understood. KLF10, a transcription factor involved in various biological processes, has an undefined role in adipose tissue and obesity. Here, we show that exercise facilitates adipocyte-derived KLF10 expression via SIRT1/FOXO1 pathway. Adipocyte-specific knockout of KLF10 blunts exercise-promoted white adipose browning, energy expenditure, fat loss, glucose tolerance in diet-induced obese male mice. Conversely, adipocyte-specific transgenic expression of KLF10 in male mice enhanced the above metabolic profits induced by exercise. Mechanistically, KLF10 interacts with FOXO1 and facilitates the recruitment of KDM4A to form a ternary complex on the promoter regions of Pnpla2 and Lipe genes to promote these key lipolytic genes expression by demethylating H3K9me3 on their promoters, which facilitates lipolysis to defend against obesity in male mice. As a downstream effector responding to exercise, adipose KLF10 could act as a potential target in the fight against obesity.